Recent Advances in Dual Triplet Ketone/Transition-Metal Catalysis - Iziumchenko, Valeriia; Gevorgyan, Vladimir (Synlett, 2023)
Dual light-excited ketone/transition-metal catalysis is a rapidly developing field of photochemistry. It allows for versatile functionalizations of C–H or C–X bonds enabled by triplet ketone acting as a hydrogen-atom-abstracting agent, a single-electron acceptor, or a photosensitizer. This review summarizes recent developments of synthetically useful transformations promoted by the synergy between triplet ketone and transition-metal catalysis.1 Introduction2 Triplet Ketone Catalysis via Hydrogen Atom Transfer2.1 Triplet Ketones with Nickel Catalysis2.2 Triplet Ketones with Copper Catalysis2.3 Triplet Ketones with Other Transition-Metal Catalysis3 Triplet Ketone Catalysis via Single-Electron Transfer4 Triplet Ketone Catalysis via Energy Transfer5 Conclusions
Keywords: dual catalysis; triplet ketone; transition-metal catalysis; photocatalysis; photosensitizer; C–H functionalization